Overcoming Barriers to Radiation Oncology Access in Low-Resource Settings in the United States - Malcolm D. Mattes, MD; Gita Suneja, MD, MS; Bruce G. Haffty, MD, MS; Cristiane Takita, MD, MBA; Matthew S. Katz, MD; Nitin Ohri, MD, MS; Curtiland Deville, Jr, MD; Malika L. Siker, MD; Henry S. Park, MD, MPH (Advances in Radiation Oncology, 2021)
Providing high-quality radiation therapy in medically underserved, low-resource environments can be challenging in the United States. During the American Society of Radiation Oncology 2020 Annual Meeting, the American Society for Radiation Oncology Committee on Health Equity, Diversity, and Inclusion hosted 4 radiation oncologists from both academic and community practices in an educational session. Speakers discussed creative ways to overcome barriers to equitable cancer care and outcomes for their vulnerable patient populations in both rural and urban settings. Successful tactics have included applying for state-sponsored grants, lobbying hospital leadership for equipment upgrades, implementing quality improvement programs specifically targeting the needs of the patient population, studying novel hypofractionation schedules, monitoring toxicities using wearable devices, and expanding transportation options.